PENGARUH EARNING PER SHARE (EPS) DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PADA PT. JASA MARGA, TBK - RAHMAWATI, RAHMAWATI; NURULHUDA, NURULHUDA; WULANDARI, WULANDARI (Universitas Mahasaraswati K. Mataram, 2024)
Return is the result obtained from investment while shares are proof of ownership. This research aims to determine the effect of earning per share and price earning ratio on stock returns at PT. jasa marga Tbk, whichis listed on the Indonesia stock exchange for the 2007-2022 period. this research is associativeresearch. The sampling techniquein this research used purposive sampling with a population of 15 years and a sample of 1 year. The data analysis method used is the classic assumption test, which contains several tests including (normality test, multicollinearity test,autocorrelation test, and heteroscedasticity test). Multiple linear regression analysis using SPSS 26. Hypothesis testing (partial test, simultaneous test). The result of this research are thad thre is a negative and significant influence on earning per share (EPS) while the price earning ratio (EPS) has a significant influence on stock returns. Whice means that together (simultanceously) the EPS and PER variabels have a significant and influential effect on stock returns